The Relationship Between Adequacy of Animal Protein Consumption and Hemoglobin Levels for Pregnant Women - Dian Fera; Maiza Duana; Enda Silvia Putri (Journal of Nutrition Science, 2021)
Adequacy of nutrition is needed by a person from the womb to adulthood. Pregnant women are one of the groups of people who are prone to malnutrition. One of the nutritional problems in pregnant women is iron anemia (Fe). Pregnant women are said to be anemic if their Hb level is <11 g / dl, anemia can also occur due to an increased need for a person's body, for example during menstruation, pregnancy and childbirth, while the iron that enters is only a little, it is highly recommended to consume food that comes from animal protein such as fish. , meat, eggs and milk. Objective: to examine the relationship between the adequacy of animal protein consumption on hemoglobin (Hb) levels of pregnant women in Johan Pahlawan District, West Aceh Regency. Methods: This study is a quantitative study with a cross sectional design. The population in this study were all pregnant women in the second and third trimesters who were recorded at Puskesmas Johan Pahlawan and Suak Ribee, West Aceh district in February 2020, totaling 165 people, the sampling technique used the purposive sampling method using the Slovin formula with a sample of 62 people. The results showed that there was a significant relationship between the consumption of animal protein intake and hemoglobin levels in pregnant women with a p value = 0.022. In conclusion, the HB level of pregnant women who consume enough animal protein is more normal than pregnant women who do not consume enough animal proteinAdequacy of nutrition is needed by a person from the womb to adulthood. Pregnant women are one of the groups of people who are prone to malnutrition. One of the nutritional problems in pregnant women is iron anemia (Fe). Pregnant women are said to be anemic if their Hb level is <11 g / dl, anemia can also occur due to an increased need for a person's body, for example during menstruation, pregnancy and childbirth, while the iron that enters is only a little, it is highly recommended to consume food that comes from animal protein such as fish. , meat, eggs and milk. Objective: to examine the relationship between the adequacy of animal protein consumption on hemoglobin (Hb) levels of pregnant women in Johan Pahlawan District, West Aceh Regency. Methods: This study is a quantitative study with a cross sectional design. The population in this study were all pregnant women in the second and third trimesters who were recorded at Puskesmas Johan Pahlawan and Suak Ribee, West Aceh district in February 2020, totaling 165 people, the sampling technique used the purposive sampling method using the Slovin formula with a sample of 62 people. The results showed that there was a significant relationship between the consumption of animal protein intake and hemoglobin levels in pregnant women with a p value = 0.022. In conclusion, the HB level of pregnant women who consume enough animal protein is more normal than pregnant women who do not consume enough animal protein